Infection control strategies for patients and accompanying persons during the COVID-19 pandemic in German hospitals: a cross-sectional study in March–April 2021. (July 2022) - Bludau, A.; Heinemann, S.; Mardiko, A.A.; Kaba, H.E.J.; Leha, A.; von Maltzahn, N.; Mutters, N.T.; Leistner, R.; Mattner, F.; Scheithauer, S.
Summary: Background: Patients are at risk of nosocomial COVID-19 infection. The role of accompanying persons/visitors as potential infection donors is not yet well researched, but the risk will be influenced by prevention measures recommended by infection control practitioners. Aim: To collect information about COVID-19 infection control strategies for patients and accompanying persons from infection control practitioners in German hospitals. Methods: A cross-sectional questionnaire was developed, ethically approved, pre-tested and formatted as an online tool. Infection control practitioners in 987 randomly selected German hospitals were invited to participate in March and April 2021. For statistical analysis, the hospitals were categorized as small (0–499 beds) or large (≥500 beds). Findings: One hundred surveys were completed (response rate: 10%). A higher proportion of large (71%) than small (49%) hospitals let patients decide freely whether to wear medical or FFP2 masks. Most hospitals reported spatial separation for COVID-19 patients and non-COVID-19 cases (38%) or additionally for suspected COVID-19 cases (53%). A separation of healthcare teams for these areas existed in 54% of the hospitals. Accompaniment bans were more prevalent in large (52%) than in small hospitals (29%), but large hospitals granted more exemptions. Conclusion: The decision as to whether to separate areas and teams seemed to depend on the hospital's structural conditions, therefore impairing the implementation of recommendations. Accompaniment regulations differ between hospital sizes and may depend on patient numbers, case type/severity and patients' requirements. In the dynamic situation of a pandemic, it can be difficult to stay up to date with findings and recommendations on infection control.